Tendencies in the development of tax administration in Slovakia - Belkovicsová, Daša; Repková, Denisa (Tendencje w rozwoju administracji podatkowej w Słowacji, 2011)
Current trends in fiscal and tax policies lie in the increasing importance of indirect taxes, simplifying tax systems to expand the tax while reducing tax rates, in the elimination of distorting effects of taxes base and duties, in the fight against tax evasion, in reducing the administrative burden on the tax and duties, as well as in mergers in tax and customs administration. Significant changes have occurred in the area of income taxation. The highest tax rate of personal income decreased on average from 67% in the 80 of the XXth century to 43% in the beginning of the XXIst century. The tax rate of corporation tax has fallen from an average of 45% to 28%. The decreased tax rates were made with the current expansion of tax base and introducing new taxes. The positive impact on economic performance is reducing the progressivity of the tax system
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2011; Nr 221, s. 55-60